ANALISIS KAPASITAS MASYARAKAT UNTUK IDENTIFIKASI TEKNOLOGI SANITASI DI KAWASAN SPESIFIK DAERAH KERING (STUDI KASUS DI KABUPATEN SUMBA BARAT DAYA NTT) - Samahatud Durriyyah (SekolahTinggi Keguruan dan Ilmu Pendidikan (STKIP), 2019)
One of the specific areas that have received less attention from the government is a specific area with a semi-arid climate conditions, where low rainfall and high evapotranspiration potential causes NTT especially Southwest Sumba Regency has a problem providing sanitation facilities, especially in the domestic waste water infrastructure. Therefore in this study wanted to know the state of the capacity of communities and the factors that affect the sustainability of the waste water sanitation technologies that can be determined in accordance with regional technology studies. Some of the factors that capacity factors examined include institutional, economic, environmental, technical, and socio cultural. To know this, do data collection using questionnaires and field observations. Next, will be analyzed by descriptive, crostab, and Analytical Hierarcy Proscess (AHP) to determine the priority factors and sub- factors that affect the sustainability of sanitation to obtain the most suitable sanitation technologies from the descriptive analysis showed that 50 % of respondents do not have sanitation facilities and conduct defecation gratuitous (BABS) in the garden and clean themselves using leaf litter. Crostab analysis can be seen that there is a relationship between level of education and income against WC ownership, how to clean themselves, and acceptance of the technology offered. AHP analysis which provides results that the most influential factor in the choice of sanitation technology is a technical factor. But the results of advice most appropriate technology for a specific area of dryland communities is cubluk, cubluk twin, and ecosan.From the overall results of the analysis obtained on sanitation technologies for arid areas is cubluk one hole with dry system.Keywords: community capacity analisys, specific dry areas, sanitation technology